A computational fluid–structure interaction analysis of coronary Y-grafts. (September 2017) - Guerciotti, Bruno; Vergara, Christian; Ippolito, Sonia; Quarteroni, Alfio; Antona, Carlo; Scrofani, Roberto
Highlights: A fluid–structure interaction analysis has been performed in realistic geometries of multiple by-passes in order to highlight the differences between the mechanical answers of venous and arterial by-passes. We found that the Von Mises vessel wall stresses are higher in the venous case, suggesting that this by-pass is more prone to formation of hyperplasia. We also found that the Residence Relative Time (RRT), a robust and single metric of low and/or oscillatory wall shear stress (WSS), is higher in the venous case, confirming that this by-pass is more prone to formation of hyperplasia. Abstract: Coronary artery disease is one of the leading causes of death worldwide. The stenotic coronary vessels are generally treated with coronary artery bypass grafts (CABGs), which can be either arterial (internal mammary artery, radial artery) or venous (saphenous vein). However, the different mechanical properties of the graft can influence the outcome of the procedure in terms of risk of restenosis and subsequent graft failure. In this paper, we perform a computational fluid–structure interaction (FSI) analysis of patient-specific multiple CABGs (Y-grafts) with the aim of better understanding the influence of the choice of bypass (arterial vs venous) on the risk of graft failure. Our results show that the use of a venous bypass results in a more disturbed flow field at the anastomosis and in higher stresses in the vessel wall with respect to the arterial one. This could explain the better long-term patency of the arterial bypasses experienced in the clinical practice.